Nexus between Digital Economy, Productivity and Growth: Evidence from Nigeria - Abdullahi, Salisu Garba; Bashir, Zainab Muhammad (Indonesian Journal of Entrepreneurship and Startups, 2024)
This study investigated the role of the digital economy on the growth of the Nigerian economy. Quarterly data on the two indicators of the digital economy which include internet penetration and ICT and some other control variables were analyzed using the Autoregressive Distributed Lag Model (ARDL). In addition to that, the Bound test is employed to determine the long-run relationship among the variables. The findings showed that the digital economy indicators are negatively impacting the growth of GDP and productivity in Nigeria. The unfavorable result can be attributed to the dominance of the government in the ICT sector. Before the 2001 liberalization agenda, the sector was entirely owned and managed by the Nigerian Government through the Nigerian Telecommunications Limited (NITEL).